The Organizational Arrangement and Strengthening of the Marine Corps - Imran Yusuf; Firdaus Firdaus; Dicky Dharwaly (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This paper aims to describe optimising the management and strengthening of the Marine Corps Command Headquarters organisation to implement resource management to realise bureaucratic reform within the Indonesian Navy. The organisational structuring and strengthening of the Marine Corps Command Headquarters aim to increase the efficiency and effectiveness of the organisation proportionally according to the needs of each task. So that it becomes the proper function and proper sizing to reduce the overlapping of tasks and internal functions of the Marine Corps Command Headquarters. Also increase the capacity of the Marine Corps Command Headquarters in carrying out the main tasks and functions in order to realise Bureaucratic Reform in the TNI AL Environment. The Marine Corps Headquarters must make changes in organisational life related to changes in behaviour, changes in the assessment system, changes in methods and ways of working.